Attentional engagement with and disengagement from food cues in Anorexia Nervosa. (March 2019) - Jonker, Nienke C.; Glashouwer, Klaske A.; Hoekzema, Albert; Ostafin, Brian D.; de Jong, Peter J.
Abstract: This study examined differences in food-related Attentional Bias (AB) between patients with Anorexia Nervosa (AN) and adolescents without an eating disorder. AB was assessed with an Attentional Response to Distal versus Proximal Emotional Information (ARDPEI) task that was specifically designed to differentiate between attentional engagement with and attentional disengagement from food. We tested if patients with AN would show less attentional engagement and less difficulty to disengage their attention from food cues than individuals without an eating disorder. Both might contribute to patients' ability to refrain from eating even in a state of starvation. Participants were adolescents with AN ( n  = 69) and a comparison group with healthy weight, matched on age and educational level ( n  = 69). No differences were found in attentional disengagement. However, patients with AN did show less attentional engagement when food cues were shown briefly (100 ms). Given that the adolescents without an eating disorder showed a significant engagement bias to food cues, the results suggest that patients with AN lack the bias involved in healthy eating behavior. Future studies should further examine the direction of the relationship between decreased attentional engagement with food cues and anorexia nervosa. Highlights: Adolescents with and without AN did not show difficulty to disengage from food cues. Adolescents without an eating disorder showed attentional engagement with food cues. Patients with AN did not show this attentional engagement bias with food cues. Patients with AN seem to lack the AB that is related to healthy eating behavior.